2022
DOI: 10.1039/d2py00101b
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the crystallinity of PCL chains by copolymerization with substituted δ/ε-lactones and its impact on the phase separation of PCL-based block copolymers

Abstract: Various substituted δ/ε-lactones have been copolymerized with ε-caprolactone (ε-CL) with the aim to inhibit the crystallization of polycaprolactone (PCL). Among the studied co-monomers, the best results were obtained with the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…In series III, C1–C3 exhibited endothermic transitions composed of two broad peaks that may have been related to different crystalline arrangements ( Figure 6 E). These transitions could have a correlation with ordered lamellar domains in the PCL blocks (higher temperature peak) in coexistence with backbone segments that suffer from reduced crystallinity due to their reduced interactions and chain folding [ 36 ]. It is worth mentioning that the percentage of ε -DL ≥ 30% mol was sufficient to achieve a transition from semi-crystalline to amorphous arrangement, as shown in C4.…”
Section: Resultsmentioning
confidence: 99%
“…In series III, C1–C3 exhibited endothermic transitions composed of two broad peaks that may have been related to different crystalline arrangements ( Figure 6 E). These transitions could have a correlation with ordered lamellar domains in the PCL blocks (higher temperature peak) in coexistence with backbone segments that suffer from reduced crystallinity due to their reduced interactions and chain folding [ 36 ]. It is worth mentioning that the percentage of ε -DL ≥ 30% mol was sufficient to achieve a transition from semi-crystalline to amorphous arrangement, as shown in C4.…”
Section: Resultsmentioning
confidence: 99%
“…Among cyclic esters, ε-caprolactone (ε-CL) is often a candidate of choice for the production of degradable plastics, benefiting from short reaction times, efficient catalytic systems, and the possibility to conduct polymerization in bulk. However, PCL is highly crystalline, so the introduction of a comonomer, such as δ-valerolactone (δ-VL), is regularly employed to inhibit PCL crystallization by impeding chain folding and alignment. , …”
Section: Introductionmentioning
confidence: 99%
“…However, PCL is highly crystalline, so the introduction of a comonomer, such as δ-valerolactone (δ-VL), is regularly employed to inhibit PCL crystallization by impeding chain folding and alignment. 25,26 Herein, we have innovatively combined the fabrication of bottlebrush polymers from modified dextrin and lactones with the fabrication of soft elastomers for wearable electronics, as shown in Scheme 1. Making native dextrin hydrophobic is a crucial component of our strategy because it transforms it into a macroinitiator for bulk ROP.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[15a] Very recently, the Bourissou group developed an efficient copolymerization of ɛ-CL with substituted δ/ɛ-lactones by employing methane sulfonic acid as a catalyst. [16] Whereas, so far the catalytic efficiency of acid-catalyzed ring-opening polymerization of ɛ-CL remains to be improved, and few examples reported the preparation of PCL with molecular weight (M n ) higher than 50k g/mol. [8a,15a] In our previous study, N,N'-bis (triflyl) phosphoramidimidates (PADIs) [17] has been demonstrated as a highly efficient organic acid catalysts for the stereoselective cationic RAFT polymerization of vinyl ethers, [17c] we thus questioned whether these acid catalysts are also effective for the ROP of lactones.…”
Section: Introductionmentioning
confidence: 99%
“…reported the use of squaric acid as an effective organocatalyst for the ROP of ϵ ‐caprolactone ( ϵ ‐CL) [15a] . Very recently, the Bourissou group developed an efficient copolymerization of ϵ ‐CL with substituted δ/ϵ‐lactones by employing methane sulfonic acid as a catalyst [16] . Whereas, so far the catalytic efficiency of acid‐catalyzed ring‐opening polymerization of ϵ ‐CL remains to be improved, and few examples reported the preparation of PCL with molecular weight ( M n ) higher than 50k g/mol [8a,15a] .…”
Section: Introductionmentioning
confidence: 99%